Small Area Estimation Anak Tidak Sekolah di Pulau Kalimantan Tahun 2023 - Luthfio Febri Trihandika; Azka Ubaidillah; Afifah Az-Zahra; Amirudin; Milla Rusydiana; Zahra Maharani (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2024)
Equitable and quality education is one of the priority goals, both nationally and internationally, in achieving the Sustainable Development Goals (SDGs). The quality of education in a region can be seen through the indicator of the percentage of out-of-school children aged 7-17 years. Kalimantan Island is one of the regions that has a high number of out-of-school children, higher than the national rate. To overcome this problem, appropriate policies are needed to improve the quality of education. Therefore, the provision of precise, accurate, and precise data is needed. This is especially true in the provision of “small area” data, at least at the district/city level. Although estimation at the kabupaten/kota level has been conducted by BPS, there is still a problem of low precision. One solution that can be applied in estimating is by using Small Area Estimation (SAE). This study aims to estimate the percentage of children aged 7-17 years who are not in school by district/city in Kalimantan Island in 2023. The author compares the estimation using Empirical Best Linear Unbiased Predictor (EBLUP) and Hierarchical Bayes Beta (HB Beta). The results show that the HB Beta estimation is better than the EBLUP estimation. Estimation using EBLUP resulted in two districts/cities with RSEs of more than 25 percent, namely Samarinda and Kutai Kartanegara. Meanwhile, estimation using HB Beta produces better precision with an overall RSE value below 25 percent